H-ATLAS/GAMA: the nature and characteristics of optically red galaxies detected at submillimetre wavelengths - Dariush, Ali A.; Hony, Sacha; Andrae, Ellen; Grootes, Meiert Willem (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. We combine Herschel/SPIRE submillimetre (submm) observations with existing multiwavelength data to investigate the characteristics of low-redshift, o
in original form 2015 February 24
Gesehen am 06.05.2020